VARIASI NILAI B VALUE DENGAN TEKNIK ADC MAPPING SEKUEN DIFFUSION WEIGHTED IMAGING UNTUK MEMBEDAKAN TINGKAT KEGANASAN TUMOR MUSKULOSKELETAL - CELINE CATHARINA ROSARI, 151610383039 (2018)
Diffusion Weighted Imaging (DWI) is functional magnetic resonance imaging technique based on changes in the Brownian motion of water molecules caused by tissue microstructure. Moreover, DWI is a noninvasive method for investigation of tumor histological content. DWI produce ADC (apparent diffusion coefficient) value when post processing and the ADC is a quantitative measure of Brownian movement and the result of ADC value affected by b value parameter. The aim of the present study to compare the diagnostic performance of DWI using b value of 800 s/mm2 and 1000 s/mm2 at 1,5 T for the evaluation of clinically musculoskeletal tumors using ADC mapping as a quantitative assessment tool. DWI was performed on 15 patient soft tissue tumors and using two b value of 800 s/mm2 and 1000 s/mm2 and the best b value to differentiating malignant and benign musculoskeletal tumors is using b value of 800 s/mm2.